Government Spending in a Simple Model of Endogeneous Growth - Barro, Robert J. (Journal of Political Economy, 1990)
One strand of endogenous-growth models assumes constant returns to a broad concept of capital. I extend these models to include tax- financed government services that affect production or utility. Growth and saving rates fall with an increase in utility-type expenditures; the two rates rise initially with productive government expenditures but subsequently decline. With an income tax, the decentralized choices of growth and saving are "too low," but if the production function is Cobb-Douglas, the optimizing government still satisfies a natural condition for productive efficiency. Empirical evidence across countries supports some of the hypotheses about government and growth.